RESERVES FOR EFFICIENT USE OF THE FINANCIAL SYSTEM ARE AT HAND - G. A. Tosunyan (Финансы: теория и практика)
Before the discussion of the monetary policy problems, it is reasonable to review our financial system as a whole. Any market, including the financial market, is characterized by the balance of supply and demand. To increase the role of banks in the economic development of the country the financial regulation specifically targeted at solving this problem is required. One of the aspects of an effective monetary policy is accessibility of various resources to banks. Along with that, the issues of the long-term support of credit institutions with resources still remain unsolved. As of the end of 2014, the Central Bank of Russia had the highest base rate of the 19 largest world economies and the highest inflation rate. What has to be done to improve the efficiency of the financial system in Russia is discussed in this paper.